WANITA KARIER DALAM KELUARGA PERSPEKTIF FEMINISME DALAM ISLAM - Zikrurahman, Muhammad (Al-Usroh, 2023)
Abstract The aim of this research is to eradicate the ignorant thoughts that still linger regarding people's beliefs that think that women do not have the right to have a career or that women are only limited to domestic matters. With the means of feminism, women can fight for their rights to have a career according to their competence as long as this does not have a negative impact on them. The method used in this research is a library research method. that library or literature study can be interpreted as a series of activities relating to methods of collecting library data, reading and taking notes and processing research materials. The results of this research show that based on feminism in Islam, women are allowed to pursue careers in accordance with women's characteristics, because Islam has principles of justice and human equality, both women and men, from slavery to traditionalism, authoritarianism (religious, economic, political or other). , racism, sexism, tribalism, slavery or anything that hinders people who want to actualize the Qur'anic vision. Then for women who have a career, of course there are conditions that must be met before starting a career.